Determinação de resíduos de agrotóxicos no leite bovino empregando método QuEChERS modificado e GC-MS/MS - Bandeira, Danieli Daiani (2012)
For providing a balanced composition, among fresh food, the milk is considered one of the most nutritionally complete, being a product very well accepted in the market with consumers of all ages. Thus, the analysis of milk quality is great importance for consumer information and verification of the parameters required by law. Considering all the problems involving the many chemicals used for several purposes in agriculture, and the possibility of these compounds directly or indirectly the milk and cause damage to population health, this work aimed to develope and validate a method for a multiresidue determination of 48 pesticides in cattle milk, using modified QuEChERS method and GC-MS/MS. The extraction procedure consisted of 5.0 mL of sample (milk) extracted with 5.0 mL of acetonitrile, acidified with 1% of acetic acid (v/v), followed by manual shaking for 1 min for partition step was used 2.0 g of anhydrous MgSO4 and 0.85 g of anhydrous sodium acetate. Manual agitation was repeated for 1 min, and subsequently it was performed centrifugation at 3400 rpm for 8 min. The dispersive clean up step consisted in add 1.0 mL of supernatant extract, 150.0 mg of anhydrous MgSO4, 125.0 mg of C18 and 62.0 mg of PSA in an eppendorf tube, which was shaked in a vortex for 1 min, centrifuged at 10000 rpm for 3 min. After centrifugation, the extract was transferred to a glass insert for the injection into the GC-MS/MS system. It was evaluated the linearity, limits of detection (LOD) and quantitation (LOQ), the matrix effect, accuracy and precision of the analytical method. The method proved to be efficient, with satisfactory results for recoveries, with values in a range between 71.1 and 117.4% for 45 of the 48 compounds analyzed. RSD values lowerd than 17,3%, values of LODi and LODm ranged between 0.3 to 3.0 μg L-1 and LOQi and LOQm ranged between 1.0 to 10.0 μg L-1. The validated method was applied for the determination of residues of 45 pesticides/degradation products in samples of milk UHT. The method developed was adequate for the analysis of pesticide residues in cattle milk, as all the validation parameters were within the limits required for validation of chromatographic methods, achieving satisfactorily the objectives outlined in this paper.